Feasibility of a revised version of the Back2School intervention: a transdiagnostic cognitive-behavioral intervention for school attendance problems - Langenskiöld, Jakob; Thastum, Mikael; Alanko, Katarina (Taylor & Francis, 2026)
School attendance problems (SAPs) are a heterogeneous clinical phenomenon with various associated etiologies, symptoms, and perpetuating factors. Most existing intervention manuals based on cognitive behavior therapy are specific to certain types of SAP. Due to this heterogeneity, transdiagnostic interventions have been recommended to address the entire spectrum of SAP with a single manual. This study aimed to evaluate the feasibility of Back2School (B2S), a transdiagnostic and modular cognitive behavior therapy intervention for SAPs in a Finnish context. The sample consisted of 16 families distributed among 5 clinicians who received training in the B2S intervention. We evaluated five distinct parameters: sample characteristics, data collection procedures and outcome measures, treatment satisfaction, acceptability, and study procedures, as well as treatment effects. The results showed an increase in school attendance after treatment, but a decrease back to pre-intervention levels at follow-up. However, the data indicated high treatment satisfaction among all respondent groups. We suggest some adaptations in data collection procedures and the recruitment process to enable B2S to be evaluated in a randomized controlled trial in the Finnish context for the treatment of SAPs.